The Structure and Analysis of Multi-power Coupling Systems for Electric Vehicle - ZHANG Shuo; ZHANG Chengning; WANG Zhifu (Kongzhi Yu Xinxi Jishu)
The scope of the power coupling system is demonstrated and pure electric power coupling system is considered. The traditional power coupling systems are summarized. The rotate speed and torque characteristics of some kind of coupling systems are compared. The advantages and disadvantages of a pure electric coupling system are pointed out, the development trend of power coupling system is forecasted and some advices for pure electric power coupling system are proposed.